2013
DOI: 10.1038/am.2013.22
|View full text |Cite
|
Sign up to set email alerts
|

Scaffolded biosensors with designed DNA nanostructures

Abstract: In addition to its fundamental function as a genetic code carrier, the utilization of DNA in various material applications has been actively explored over the past several decades. DNA is intrinsically an excellent type of self-assembly nanomaterial owing to its predictable base-pairing, high chemical stability and the convenience it possesses for synthesis and modification. Because of these unparalleled properties, DNA is widely used as excellent recognition elements in biosensors and as unique building block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
111
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 119 publications
(113 citation statements)
references
References 79 publications
2
111
0
Order By: Relevance
“…37 In addition, ATP could bind to an in vitro-selected Enzymatic performance of ATP over a broad temperature range Y Lin et al 27-base anti-ATP aptamer with high affinity and could induce the aptamer to undergo a conformational change from random coil to tertiary structure. 40 Inspired by the unique properties of ATP, we found that ATP could promote the catalytic activity of the Au-SiO 2 catalyst within a fairly broad range of operating temperatures (Figures 2b and c). As shown in Figure 2c, the activity of the nanocatalyst shows a linear increase along with the temperature elevation from 25 to 85 1C, and this is in sharp contrast to that obtained without ATP (Figures 2a and c) and to that of the HRP enzyme (Supplementary Figure S5).…”
Section: Resultsmentioning
confidence: 93%
“…37 In addition, ATP could bind to an in vitro-selected Enzymatic performance of ATP over a broad temperature range Y Lin et al 27-base anti-ATP aptamer with high affinity and could induce the aptamer to undergo a conformational change from random coil to tertiary structure. 40 Inspired by the unique properties of ATP, we found that ATP could promote the catalytic activity of the Au-SiO 2 catalyst within a fairly broad range of operating temperatures (Figures 2b and c). As shown in Figure 2c, the activity of the nanocatalyst shows a linear increase along with the temperature elevation from 25 to 85 1C, and this is in sharp contrast to that obtained without ATP (Figures 2a and c) and to that of the HRP enzyme (Supplementary Figure S5).…”
Section: Resultsmentioning
confidence: 93%
“…As a universal sensing system, this DNA machine can be readily constructed to be an electrochemical or electrochemiluminescence biosensor by only changing the signal unit (MB in this work) to corresponding signal reporters (electrochemical MB or electrochemiluminescence MB). 39,40 Our ongoing work will demonstrate the applicability of this ESQM-based electrochemical biosensor combined with DNA nanostructure in the detection of cancer biomarkers such as microRNA and DNA methylation. …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, DNA is increasingly used to create nano-scaffolds on surfaces for controlling probe density, position, and accessibility with nanometric resolution [87], hence enabling to minimize the effect of competing interaction with the surface. Furthermore, selected sequences can act as aptamers capable of binding specific targets, ranging from metal ions [88] to proteins [72,89].…”
Section: Dna-based Amplification Strategiesmentioning
confidence: 99%